Auditing for privacy in threshold PKE e-voting. (13th March 2017) - Kiayias, Aggelos; Zacharias, Thomas; Zhang, Bingsheng
Abstract : Purpose: This paper aims to investigate the importance of auditing for election privacy via issues that appear in the state-of-the-art implementations of e-voting systems that apply threshold public key encryption (TPKE) in the client such as Helios and use a bulletin board (BB). Design/methodology/approach: Argumentation builds upon a formal description of a typical TPKE-based e-voting system where the election authority (EA) is the central node in a star network topology. The paper points out the weaknesses of the said topology with respect to privacy and analyzes how these weaknesses affect the security of several instances of TPKE-based e-voting systems. Overall, it studies the importance of auditing from a privacy aspect. Findings: The paper shows that without public key infrastructure (PKI) support or – more generally – authenticated BB "append" operations, TPKE-based e-voting systems are vulnerable to attacks where the malicious EA can act as a man-in-the-middle between the election trustees and the voters; hence, it can learn how the voters have voted. As a countermeasure for such attacks, this work suggests compulsory trustee auditing. Furthermore, it analyzes how lack of cryptographic proof verification affects the level of privacy that can be provably guaranteed in a typical TPKE e-voting system. Originality/value: As opposed to the extensively studied importance of auditing to ensure election integrity, the necessity of auditing to protect privacy in an e-voting system has been mostly overlooked. This paper reveals design weaknesses present in noticeable TPKE-based e-voting systems that can lead to a total breach of voters' privacy and shows how auditing can be applied for providing strong provable privacy guarantees.